Muscle mechanical response to exercise with active vs. passive rest - Rodrigo Bueno-Russo; Jorge Velázquez Saornil; Germán Díaz-Ureña; Zacarías Sánchez Milá; Raúl Frutos Llanes; José Manuel Barragán Casas; David Rodríguez Sanz (Elsevier, 2024)
Introduction: the muscular response on the main muscles of the propulsive phase of the upper limb in the crawl swimming style has been evaluated by means of tensiomyography (TMG), which was carried out through three parameters: activation time (Td), contraction time (Tc) and maximum deformation (Dm).The aim of this study is to evaluate the hypothesis of changes produced between lactic resistance training with passive rest and lactic resistance training with active rest. Material and methods: experimental study with ninety swimmers in the crawl stroke, with a mean age of 20 years. The session with passive recovery and the session with active recovery presented results with significant changes after the development of each of them in the Tc in the three muscles analysed, being in the Pectoralis Major (PM), p = 0.001, in the Latissimus Dorsi (LD), p = 0.01 and in the Tríceps Brachii (TB), p = 0.047. Conclusion: According to the results it can be deduced that lactic resistance training with passive rest and with active rest do not influence the muscle response if we compare both trainings. Only one of the Tc values changes, while the latissimus dorsi muscle also shows changes in Td.